2020
DOI: 10.1128/msphere.00117-20
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Colistin-Resistant Escherichia coli with Chromosomally Carried mcr-1 in Healthy Residents in Vietnam

Abstract: The wide distribution of colistin-resistant bacteria in developing countries has become a common phenomenon. To understand the mechanisms underlying their distribution, we studied the mcr genetic background of colistin-resistant Escherichia coli isolates from the fecal microbiota of healthy human residents from a community in Vietnam with a high prevalence of colistin-resistant E. coli with mcr. Fifty-seven colistin-resistant isolates were obtained from 98 residents; one isolate was collected from each individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…Another alarming rate for colistin resistance in Egypt was reported among cancer patients, where 8.8% of Klebsiella pneumoniae (K. pneumoniae) and E. coli strains were colistin-resistant [63]. In agreement with different reports, in our study, resistance to colistin was mediated by the presence of the mcr-1 gene, which is responsible for the addition of phosphoethanolamine to the lipid A fraction of the cell wall [64][65][66]. However, we did not test the presence of the recently reported types of mcr such as mcr 6-10 or the pmrA/B and phoP/Q genes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another alarming rate for colistin resistance in Egypt was reported among cancer patients, where 8.8% of Klebsiella pneumoniae (K. pneumoniae) and E. coli strains were colistin-resistant [63]. In agreement with different reports, in our study, resistance to colistin was mediated by the presence of the mcr-1 gene, which is responsible for the addition of phosphoethanolamine to the lipid A fraction of the cell wall [64][65][66]. However, we did not test the presence of the recently reported types of mcr such as mcr 6-10 or the pmrA/B and phoP/Q genes.…”
Section: Discussionsupporting
confidence: 91%
“…In Portugal, screening of 100 rectal swabs from pigs revealed 98 mcr-1-positive isolates [71]. It is possible that persistent exposure to low levels of colistin, such as those originating from the use of colistin-containing poultry food, led to the development of colistin resistance [64].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other mcr variants appeared in China as well as Europe and the USA (Rebelo et al 2018;Gharaibeh and Shatnawi 2019;Borowiak et al 2020). Recent study demonstrated that some Escherichia coli carried chromosomal mcr-1 (Yamaguchi et al 2020). The rapid spread of mcr-1 associated with humans and animals has been observed globally (von Wintersdorff et al 2016;Al-Tawfiq et al 2017;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the primary travel destination being Vietnam was associated with a higher risk of acquisition of colistin resistance genes. Yamaguchi et al, revealed a high percentage (36.8%) of colistin-resistant E. coli carrying chromosomal mcr-1 in the faecal microbiota of a community of Vietnam residents [58]. In this study, we revealed that 40% of students who participated in a school renovation project in Vietnam became carriers of mcr genes.…”
Section: Discussionmentioning
confidence: 50%